Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi dan Kecerdasan Emosional terhadap Kepuasan Kerja pada Karyawan Toserba Mayga Kabupaten Brebes - Novia Divayan Safitri; Suhana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of transformational leadership style, organizational culture and emotional intelligence on employee job satisfaction. This research was conducted at the Mayga Department Store, Brebes Regency, using a purposive sampling technique. The sample in this study consisted of 100 respondents obtained from distributing questionnaires. This testing stage consists of instrument testing consisting of validity and reliability tests, model testing and hypothesis testing using IBM SPSS 23. Based on the research results, it shows that transformational leadership style has a positive and significant influence on job satisfaction. Organizational culture also has a positive and significant influence on job satisfaction. However, emotional intelligence has no effect on job satisfaction.